1977
DOI: 10.1021/bi00630a005
|View full text |Cite
|
Sign up to set email alerts
|

Purification using polyethylenimine precipitation and low molecular weight subunit analyses of calf thymus and wheat germ DNA-dependent RNA polymerase II

Abstract: DNA-dependent RNA polymerase II from calf thymus has been successfully purified using polythylenimine precipitation. Thus, 5-6 mg of nearly homogeneous homogeneous trna polymerase II (greater than 96% pure) can be prepared from 1 kg of calf thymus with three chromatography steps following extraction and precipitation of the enzyme from the polyethylenimine pellet. This procedure eliminates the high salt extraction of chromatin previously used in purification of this enzyme and makes possible the large scale pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(104 citation statements)
references
References 27 publications
7
97
0
Order By: Relevance
“…Purification of RNA polymerase II from calf thymus was carried out by a modification ofthe method of Hodo and Blatti (28), except that all buffers contained 0.1% Nonidet P-40. Fractions from the phosphocellulose column containing RNAP II activity were pooled and applied to a heparin-agarose column equilibrated with buffer containing 60 mM ammonium sulfate.…”
Section: Methodsmentioning
confidence: 99%
“…Purification of RNA polymerase II from calf thymus was carried out by a modification ofthe method of Hodo and Blatti (28), except that all buffers contained 0.1% Nonidet P-40. Fractions from the phosphocellulose column containing RNAP II activity were pooled and applied to a heparin-agarose column equilibrated with buffer containing 60 mM ammonium sulfate.…”
Section: Methodsmentioning
confidence: 99%
“…However, analysis of specific transcription products by polyacrylamide gel electrophoresis revealed that these enzyme preparations contained a small amount of RNA polymerase III activity resistant to 2 pLg of a-amanitin per ml. (Residual RNA polymerase III has also been observed [51] in RNA polymerase II preparations purified by the method of Hodo and Blatti [27] were obtained from D. Bentley and M. Groudine. The templates used for transcription were generated by restriction digestion of the plasmid at a unique site followed by addition of single-stranded polydeoxycytidylate extensions of 30 to 100 residues by using terminal deoxynucleotidyl transferase (28).…”
Section: Methodsmentioning
confidence: 99%
“…While a number of groups have purified human pol II and associated proteins (26,32,36,45,51; also reviewed in references 57 and 70), it has been clear from a comparison of results that the number, molecular weight, and quantity of copurified proteins are somewhat variable between different groups and starting sources of material, and it was previously uncertain whether a human RPB4 homolog existed. The ϳ27 kDa hsRPB7 species and ϳ18-to 19-kDa native hsRPB4 species described in this work are now shown to be present in affinity-purified pol II, conclusively demonstrating their functionality in mammalian cells.…”
Section: Conservation Of Hsrpb4 Mmrpb4 and Rpb4 Subunitsmentioning
confidence: 99%